Anthropometric Measurements of Athletes Performed by Teachers of the Faculty for Sport and Physical Education, University of Montenegro in 2017 - Svetlana Mandic (Journal of Anthropology of Sport and Physical Education, 2021)
The Center for Diagnostics in Sport, which is an integral part of the Faculty for Sport and Physical Education University of Montenegro, was established in 2017. It was accredited by the Ministry of Science and systematized by the University of Montenegro. The main function of the Center is to conduct research that will contribute to the improvement of scientific work in the field of sports sciences, as well as scientific branches and disciplines that are directly or indirectly related to sport and sports science. During the first year of its work, the Center justified its purpose and from May 20 to October 27 teachers of the Faculty for Sport and Physical Education, carried out 40 anthropometric measurements having tested individuals, clubs and national teams of different age groups from the country and abroad. In this paper, we classified the performed tests according to the countries where the athletes come from, as well as according to sports; separately for national teams, clubs and individuals. It was determined that the majority of the tested athletes were from Montenegro; even 22 national teams passed the tests. It was also determined from which sports there was the largest number of tested participants, as well as who the tested individuals were. Further research, which will include anthropometric measurements from 2018, can be based on this research. In addition, this research is significant because it gives an overview of all tests performed during the first year of work of the Center for Diagnostics in Sport.